Student Behaviour Transformation in Digital Learning: A Study of The Effect of Game Duration on Students' Critical Thinking Skills - Dearlina Sinaga; Sanggam Pardede; Nova Yunita Sari; Marlita Sinaga (LPPM Universitas PGRI Sumatera Barat, 2025)
This study will explore the duration of game use most frequently by students, as well as the theories that support the effectiveness of games in improving critical thinking skills. This study aims to determine the Transformation of Student Behavior in Digital Learning: A Study of the Effect of Game Use Duration on Critical Thinking Skills of Students at SMK Negeri 1 Medan. This study uses a descriptive quantitative method with a Structural Equation Model (SEM) approach. This method is used to analyze the relationship between latent variables, namely the type and duration of game use and indicators of students' critical thinking. The population in this study were students of SMK Negeri 1 Medan who actively use games in their daily lives. The type of Educational Game (JGE) has the strongest influence on the development of students' higher-order thinking skills, especially in the Reasoning and Systems Thinking aspects. The duration of play (both educational and entertainment) does not have a significant effect on the critical thinking skills of SMK students. The Type of Entertainment Game (JGH) only makes a small contribution to students' cognitive development and tends to be recreational. The transformation of students' thinking behavior occurs when playing games shifts orientation from entertainment to a reflective and strategic learning process. The novelty of this research SEM model shows that educational games can be an effective digital learning medium in developing critical, systemic, and problem-solving thinking skills — core competencies of vocational school students to face the technology-based world of work